PROBING FINANCIAL LITERACY LEVELS IN INDIA'S IT SECTOR: AN ANALYTICAL STUDY OF PERSONAL FINANCIAL ACUMEN - Sreelakshmi SP; K.Vijayarani (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This study explores the financial literacy levels among professionals in India's IT sector, emphasizing their personal financial acumen. As a rapidly evolving industry characterized by high incomes and dynamic career trajectories, the IT sector offers a unique demographic for analyzing financial behavior and decision-making skills. The research investigates core dimensions of financial literacy, including budgeting, savings, investment strategies, debt management, and retirement planning. Using a mixed-methods approach, the study collects quantitative data through surveys and qualitative insights via interviews to evaluate how IT professionals manage their finances amidst economic uncertainties. The findings reveal critical gaps in financial understanding, despite access to resources and education. The study also identifies correlations between financial literacy and factors such as age, income, education, and work experience. Recommendations for enhancing financial literacy through targeted programs and institutional interventions are proposed to foster financial well-being among IT professionals.